2022
DOI: 10.1111/medu.14726
|View full text |Cite
|
Sign up to set email alerts
|

Patient involvement in assessment of postgraduate medical learners: A scoping review

Abstract: Context Competency‐based assessment of learners may benefit from a more holistic, inclusive, approach for determining readiness for unsupervised practice. However, despite movements towards greater patient partnership in health care generally, inclusion of patients in postgraduate medical learners' assessment is largely absent. Methods We conducted a scoping review to map the nature, extent and range of literature examining the inclusion (or exclusion) of patients within the assessment of postgraduate medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(56 citation statements)
references
References 93 publications
(559 reference statements)
0
48
0
Order By: Relevance
“…The training of doctors is a process of enculturation and 'tacit socialization'. 1 Instilling a sense of identity as a medical professional is, in fact, an explicit goal of many medical education programmes. Social identity approaches suggest that group membership influences an individual's self-concept and that group norms tend DOI: 10.1111/medu.14788…”
Section: Orcidmentioning
confidence: 99%
See 2 more Smart Citations
“…The training of doctors is a process of enculturation and 'tacit socialization'. 1 Instilling a sense of identity as a medical professional is, in fact, an explicit goal of many medical education programmes. Social identity approaches suggest that group membership influences an individual's self-concept and that group norms tend DOI: 10.1111/medu.14788…”
Section: Orcidmentioning
confidence: 99%
“…Although clinicians, as the central actors in assessment systems, have expressed uncertainty and concerns regarding ability, expertise and potential bias of patients in assessment, 2 studies have shown that clinicians themselves are not totally free of bias in their judgement 3 . As such, Khalife et al 1 reignite the debate about the usefulness of patient involvement in assessment within medical education. In this commentary, I will further contrast and compare the decision making of patients (standardised or real) with the processes employed by clinically trained examiners in an effort to help elucidate the usefulness of the patient's voice in competency‐based assessment and guide future research in this area.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Person-centredness demands that biomedical and experiential expertise coalesce, and it makes intuitive sense that fulfilling the promise of person-centredness depends on involving patients in teaching and assessment. 11 Many patients are eager to do this work, and we have had the privilege of participating in both patient-level and institutional efforts aimed at meaningfully including patients in teaching and assessment. We are heartened that stubborn professional values may be slowly starting to budge, making room for opportunities to transform person-centredness from an aspiration into a fundamental feature of training and care.…”
mentioning
confidence: 99%
“…Person‐centredness demands that biomedical and experiential expertise coalesce, and it makes intuitive sense that fulfilling the promise of person‐centredness depends on involving patients in teaching and assessment 11 . Many patients are eager to do this work, and we have had the privilege of participating in both patient‐level and institutional efforts aimed at meaningfully including patients in teaching and assessment.…”
mentioning
confidence: 99%